2019
DOI: 10.3390/md17100542
|View full text |Cite
|
Sign up to set email alerts
|

Magnificamide, a β-Defensin-Like Peptide from the Mucus of the Sea Anemone Heteractis magnifica, Is a Strong Inhibitor of Mammalian α-Amylases

Abstract: Sea anemones’ venom is rich in peptides acting on different biological targets, mainly on cytoplasmic membranes and ion channels. These animals are also a source of pancreatic α-amylase inhibitors, which have the ability to control the glucose level in the blood and can be used for the treatment of prediabetes and type 2 diabetes mellitus. Recently we have isolated and characterized magnificamide (44 aa, 4770 Da), the major α-amylase inhibitor of the sea anemone Heteractis magnifica mucus, which shares 84% seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 57 publications
(70 reference statements)
1
24
0
Order By: Relevance
“…Research on the TRPV1 inhibitors has continued on this species, from which the other three homologous peptides, τ-SHTX-Hcr2c (APHC2), τ-SHTX-Hcr2d (APHC3) and HCRG21, have been isolated [ 126 , 129 ]. These three peptides showed analgesic activity in an in vivo heat stimulation model [ 130 , 139 ]…”
Section: Venoms Of Cnidariamentioning
confidence: 99%
See 3 more Smart Citations
“…Research on the TRPV1 inhibitors has continued on this species, from which the other three homologous peptides, τ-SHTX-Hcr2c (APHC2), τ-SHTX-Hcr2d (APHC3) and HCRG21, have been isolated [ 126 , 129 ]. These three peptides showed analgesic activity in an in vivo heat stimulation model [ 130 , 139 ]…”
Section: Venoms Of Cnidariamentioning
confidence: 99%
“…Helianthamide, a potent inhibitor of human pancreatic α-amylase produced by the Caribbean Sea anemone Stichodactyla helianthus , is the first representative of a new group of amylase inhibitors that was isolated in 2016 [ 175 ], while Magnificamide is the second representative of such inhibitors. Both peptides appear to be promising compounds to manage obesity and type 2 diabetes [ 139 ]. The biological relevance of the presence of α-amylase inhibitors in the Cnidaria venoms remains largely unexplained.…”
Section: Venoms Of Cnidariamentioning
confidence: 99%
See 2 more Smart Citations
“…Magnificamide, the major α-amylase inhibitor, comprising of 44 amino acid residues (4770 Da), was isolated from the sea anemone Heteractis magnifica mucus. Sintsova and colleagues from PIBOC and University of Lueven, Belgium, have reported that the recombinant magnificamide inhibits porcine and human saliva α-amylases in low nanomolar concentrations and could be considered as a promising drug candidate for the type 2 diabetes treatment [8].…”
Section: Ofmentioning
confidence: 99%